Pengaruh Ukuran Perusahaan, Leverage, dan Profitabilitas terhadap Nilai Perusahaan pada Subsektor Food and Beverages yang Terdaftar di Bursa Efek Indonesia Tahun 2020–2022 - Nabila, Bella Rizky Putri (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2024)
This study examines the effects of firm size, leverage, and profitability on firm value in food and beverage subsector companies listed on the Indonesia Stock Exchange during the 2020–2022 period. The study employs a quantitative approach using secondary data obtained from company financial statements. The population consisted of 47 food and beverage companies, while the sample was selected through purposive sampling and comprised 20 companies. Data were analyzed using multiple linear regression with SPSS version 25. The results show that firm size has no significant effect on firm value, while leverage and profitability have positive and significant effects on firm value. Simultaneously, firm size, leverage, and profitability significantly affect firm value. The adjusted coefficient of determination is 67.6%, indicating that the three independent variables explain 67.6% of the variation in firm value.